Akulturasi Suku Bugis dan Suku Lauje: Studi Komunikasi Antar Budaya Desa Balukang Kabupaten Donggala - Haikal, Mohammad (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
The aims of this study are: (1) To explain the acculturation that occurred (a study of intercultural communication between the Bugis and Lauje tribes in Balukang Village). (2) To explain the acculturation factors that occur between different ethnic groups (a study of intercultural communication between the Bugis and Lauje tribes in Balukang Village). This type of research is descriptive qualitative, namely by examining the data obtained from the field and then describing or describing the results of the research. The informants of this research are people who are selected based on certain considerations that they are considered competent to answer the researcher's questions. Primary data were obtained through participant observation and in-depth interviews. Secondary data is obtained through literature study in the form of books, journals and so on related to the problem under study. The results obtained indicate that acculturation has occurred (a study of intercultural communication between the Bugis and Lauje tribes in Balukang Village).